MORTALITY RATES FOLLOWING DEUTECTOMY IN ANAESTHETIZED AND NON-ANAESTHETIZED DAY OLD CHICKS (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted in an attempt to standardize a technique of surgical removal of the residual yolk sac in newly hatched chick. Fifteen Attempts were made (7 using Ether as anaesthetizing agent and 8 without anesthesia). Mortality rates among the anaesthetized chicks ranged between 40-87.5% (average 56.7 %), which in the non- anaesthetized group was between 0-60% (average 10.3%) . The mortality rates decreased with increasing the experience (number of trials) in the nonanaesthetized ones.